Osmolality and Non-Structural Carbohydrate Composition in the Secondary Phloem of Trees across a Latitudinal Gradient in Europe - Lintunen, Anna; Paljakka, Teemu; Jyske, Tuula; Peltoniemi, Mikko; Sterck, Frank; von Arx, Georg; Cochard, Hervé; Copini, Paul; Caldeira, Maria C.; Delzon, Sylvain; Gebauer, Roman; Grönlund, Leila; et al. (Frontiers in Plant Science, 2016)
Phloem osmolality and its components are involved in basic cell metabolism, cell growth, and in various physiological processes including the ability of living cells to withstand drought and frost. Osmolality and sugar composition responses to environmental stresses have been extensively studied for leaves, but less for the secondary phloem of plant stems and branches. Leaf osmotic concentration and the share of pinitol and raffinose among soluble sugars increase with increasing drought or cold stress, and osmotic concentration is adjusted with osmoregulation. We hypothesize that similar responses occur in the secondary phloem of branches. We collected living bark samples from branches of adult Pinus sylvestris, Picea abies, Betula pendula and Populus tremula trees across Europe, from boreal Northern Finland to Mediterranean Portugal. In all studied species, the observed variation in phloem osmolality was mainly driven by variation in phloem water content, while tissue solute content was rather constant across regions. Osmoregulation, in which osmolality is controlled by variable tissue solute content, was stronger for Betula and Populus in comparison to the evergreen conifers. Osmolality was lowest in mid-latitude region, and from there increased by 37% towards northern Europe and 38% towards southern Europe due to low phloem water content in these regions. The ratio of raffinose to all soluble sugars was negligible at mid-latitudes and increased towards north and south, reflecting its role in cold and drought tolerance. For pinitol, another sugar known for contributing to stress tolerance, no such latitudinal pattern was observed. The proportion of sucrose was remarkably low and that of hexoses (i.e. glucose and fructose) high at mid-latitudes. The ratio of starch to all non-structural carbohydrates increased towards the northern latitudes in agreement with the build-up of osmotically inactive C reservoir that can be converted into soluble sugars during winter acclimation in these cold regions. Present results for the secondary phloem of trees suggest that adjustment with tissue water content plays an important role in osmolality dynamics. Furthermore, trees acclimated to dry and cold climate showed high phloem osmolality and raffinose proportion.